Genome mapping with anchored clones: theoretical aspects. - Ewens, W; Bell, C; Donnelly, P; Dunn, P; Matallana, E; Ecker, JR (1991)
As part of our effort to construct a physical map of the genome of Arabidopsis thaliana we have made a mathematical analysis of our experimental approach of anchoring yeast artificial chromosome clones with genetically mapped RFLPs and RAPDs. The details of this analysis are presented and their implications for mapping the Arabidopsis genome are discussed.